Question about Super Tutor Trigonometry (ESDTRIG) for PC

csc(x)=1/sin(x)

sec(x)=1/cos(x)

csc(x)/sec(x)=(1/sin(x))*(cos(x)=cot(x)

csc(x)*cot(x)/sec(x)=(cot(x))^2=(tan(x))^(-2)

sec(x)=1/cos(x)

csc(x)/sec(x)=(1/sin(x))*(cos(x)=cot(x)

csc(x)*cot(x)/sec(x)=(cot(x))^2=(tan(x))^(-2)

Jul 12, 2014 | Super Tutor Trigonometry (ESDTRIG) for PC

I worked out the algebra leaving out a few simple steps (special binomial products, Pythagorean theorem in trigonometry, definition of secant and co-secant functions). I am inserting the answer as a set of png pictures. However I am not sure how it will look.

Sep 21, 2013 | ValuSoft Bible Collection (10281) for PC

[tan(x)]^2 or tan^2 x

Sep 16, 2013 | Super Tutor Trigonometry (ESDTRIG) for PC

Let's start with a little background.

The cot(x) is also known as the cotangent(x) and it equals 1/tan(x) which equals cos(x)/sin(x). I'm showing these formulas because your calculator may not have a cot button but it will probably have buttons for tan, cos, and sin.

Your calculator may also have buttons for tan-1, cos-1 and sin-1. These are the inverse functions for tan, cos, and sin. If you enter a number and then push the tan-1 button, the result is the angle whose tangent is the entered number. For example, it you enter 1 and push the tan-1 button the answer will be 45 deg because tan (45 deg) = 1.

Now let's look at the problem, cot(x) = -0.6.

The first thing we need to know is do you want the answer in degrees or radians? Your calculator will have both modes. The default mode when you first turn it on is probably degrees. If this problem is in radians you will need to change the mode of your calculator over to radians before we start.

If cot(x) = -0.6, then tan(x) = 1/-0.6 from the formula I showed in the background section.

This means tan(x) = -1.6666666...

Now we just enter -1.66666667 and hit the tan-1 button to get the answer.

If we're operating in radians the answer is -1.0307 radians.

If we're operating in degrees the answer is -59.036 deg.

I hope this helps you out.

Dec 06, 2011 | SoftMath Algebrator - Algebra Homework...

you can follow this link and can get the solution http://mathforum.org/dr.math/faq/formulas/faq.trig.html

May 31, 2010 | Super Tutor Trigonometry (ESDTRIG) for PC

I shall attempt :D

1) cosec A + cot A = 3

we know that (cot A)^2 + 1 = (cosec A)^2

Hence, (cosec A)^2 - (cot A)^2 = 1

thus, (cosec A + cot A) (cosec A - cot A) = 1

3 (cosec A - cot A) = 1

(cosec A - cot A) = 1/3

(cosec A - cot A) = 1/3

(cosec A + cot A) = 3

Summing them, 2 cosec A = 3 1/3

cosec A = 6 2/3 = 5/3

sin A = 0.15

Thus, cos A = sqrt (1 - (sin A)^2) = 0.989

2) Prove that (1+tan x - sec x)(1 + cot x + cosec x) =2

expand

LHS= 1 + cot x + cosec x + tan x + 1 + tan x cosec x - sec x - sec x cot x - sec x cosec x

We can calculate that

tan x cosec x = sec x (since tan x = sin x / cos x)

sec x cot x = cosec x

so the above is

LHS = 1 + cot x + cosec x + tan x + 1 + sec x - sec x - cosec x - sec x cosec x

LHS = 2 + cot x + tan x - sec x cosec x

LHS = 2 + cos x / sin x + sin x / cos x - 1 / (sin x cos x)

LHS = 2 + [{cos x}^2 + {sin x}^2 - 1] / (sin x cos x)

LHS = 2 (proved)

1) cosec A + cot A = 3

we know that (cot A)^2 + 1 = (cosec A)^2

Hence, (cosec A)^2 - (cot A)^2 = 1

thus, (cosec A + cot A) (cosec A - cot A) = 1

3 (cosec A - cot A) = 1

(cosec A - cot A) = 1/3

(cosec A - cot A) = 1/3

(cosec A + cot A) = 3

Summing them, 2 cosec A = 3 1/3

cosec A = 6 2/3 = 5/3

sin A = 0.15

Thus, cos A = sqrt (1 - (sin A)^2) = 0.989

2) Prove that (1+tan x - sec x)(1 + cot x + cosec x) =2

expand

LHS= 1 + cot x + cosec x + tan x + 1 + tan x cosec x - sec x - sec x cot x - sec x cosec x

We can calculate that

tan x cosec x = sec x (since tan x = sin x / cos x)

sec x cot x = cosec x

so the above is

LHS = 1 + cot x + cosec x + tan x + 1 + sec x - sec x - cosec x - sec x cosec x

LHS = 2 + cot x + tan x - sec x cosec x

LHS = 2 + cos x / sin x + sin x / cos x - 1 / (sin x cos x)

LHS = 2 + [{cos x}^2 + {sin x}^2 - 1] / (sin x cos x)

LHS = 2 (proved)

May 12, 2009 | ValuSoft Bible Collection (10281) for PC

hi,

try to go to this page and you will find lots of ebook related to what you are looking for.

http://www.pdf-search-engine.com/identities-trigonometry--pdf.html

thanks. rate me please

try to go to this page and you will find lots of ebook related to what you are looking for.

http://www.pdf-search-engine.com/identities-trigonometry--pdf.html

thanks. rate me please

Mar 22, 2009 | Educational & Reference Software

sec^4X- sec^2X = 1/cot^4X + 1/cot^2X

RHS

1/cot^4X + 1/cot^2X

=1/(Cos^4X/Sin^4X) + 1/(Cos^2X/Sin^2X)

=Sin^4X/Cos^4X + Sin^2X/Cos^2X

=Sin^4X/Cos^4X + Cos^2X.Sin^2X/Cos^4X

=Sin^2X/Cos^4(Sin^2X + Cos^2X)

=Sin^2X/Cos^4X

=(1-Cos^2X)/Cos^4X

=1/Cos^4X - Cos^2X/Cos^4X

=1/Cos^4X - 1/Cos^2X

=Sec^4X - Sec^2X

=LHS

RHS

1/cot^4X + 1/cot^2X

=1/(Cos^4X/Sin^4X) + 1/(Cos^2X/Sin^2X)

=Sin^4X/Cos^4X + Sin^2X/Cos^2X

=Sin^4X/Cos^4X + Cos^2X.Sin^2X/Cos^4X

=Sin^2X/Cos^4(Sin^2X + Cos^2X)

=Sin^2X/Cos^4X

=(1-Cos^2X)/Cos^4X

=1/Cos^4X - Cos^2X/Cos^4X

=1/Cos^4X - 1/Cos^2X

=Sec^4X - Sec^2X

=LHS

Feb 02, 2009 | Super Tutor Trigonometry (ESDTRIG) for PC

THIS PROBELM IS TO DIFFICULT SO PLEASE SLOVE THIS PROBELM

Oct 07, 2008 | Educational & Reference Software

Change csc to 1/sin. Find a common denominator and add the two left terms.

1/sin - sin = (1 -sin^2)/sin. Rewrite formula

(1 - sin^2)/sin = cos^2/sin Divide out the /sin.

1 - sin^2 = cos^2 Rearange.

1 = cos^2 + sin^2 Yes, that's true. It's like the Pythagorean formula.

1/sin - sin = (1 -sin^2)/sin. Rewrite formula

(1 - sin^2)/sin = cos^2/sin Divide out the /sin.

1 - sin^2 = cos^2 Rearange.

1 = cos^2 + sin^2 Yes, that's true. It's like the Pythagorean formula.

May 22, 2008 | Super Tutor Trigonometry (ESDTRIG) for PC

169 people viewed this question

Usually answered in minutes!

×